레이다 응용을 위한 이중 완전 셔플 네트워크 기반 Scalable FFT 프로세서 - 김건호; Geonho Kim; 허진무; Jinmoo Heo; 정용철; Yongchul Jung; 정윤호; Yunho Jung (한국항행학회논문지, 2018)
레이다 시스템의 경우, 타겟의 거리와 속도를 추출하기 위해 FFT (fast Fourier transform) 연산이 필수적으로 요구되며, 실시간 구현을 위해 고속으로 동작하는 FFT 프로세서의 설계가 필요하다. 고속 FFT 프로세서를 위한 하드웨어 구조로 완전 셔플 네트워크(perfect shuffle network) 구조가 적합하며, 특히 초고속 연산을 위해 radix-4 기반의 이중 완전 셔플 네트워크 (twice perfect shuffle network) 구조가 가장 적절하고 볼 수 있다. 더불어, 다양한 속도 해상도를 요구하는 레이다 응용을 고려할 때, FFT 프로세서는 가변길이 FFT 연산을 지원할 필요가 있다. 이에 본 논문에서는 8~1024 포인트의 가변 길이 연산을 지원하는 이중 완전 셔플 네트워크 기반의 FFT 알고리즘을 제안하였으며, 이의 하드웨어 구조 설계 및 구현 결과를 제시한다. 제안된 FFT 프로세서는 HDL (hardware description language)을 활용하여 RTL (register transfer level) 설계가 수행되었으며, 0.65 μm CMOS 공정을 활용하여 논리 합성한 결과, 총 3,293K개의 논리 게이트로 구현 가능함을 확인 할 수 있었다. In radar systems, fast Fourier transform (FFT) operation is necessary to obtain the range and velocity of target, and the design of an FFT processor which operates at high speed is required for real-time implementation. The perfect shuffle network is suitable for high-speed FFT processor. In particular, twice perfect shuffle network based on radix-4 is preferred for very high-speed FFT processor. Moreover, radar systems that requires various velocity resolution should support scalable FFT points. In this paper, we propose a 8~1024-point scalable FFT processor based on twice perfect shuffle network algorithm and present hardware design and implementation results. The proposed FFT processor was designed using hardware description language (HDL) and synthesized to gate-level circuits using 0.65μm CMOS process. It is confirmed that the proposed processor includes logic gates of 3,293K.